3b+7=-2b-16

Simple and best practice solution for 3b+7=-2b-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b+7=-2b-16 equation:


Simplifying
3b + 7 = -2b + -16

Reorder the terms:
7 + 3b = -2b + -16

Reorder the terms:
7 + 3b = -16 + -2b

Solving
7 + 3b = -16 + -2b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '2b' to each side of the equation.
7 + 3b + 2b = -16 + -2b + 2b

Combine like terms: 3b + 2b = 5b
7 + 5b = -16 + -2b + 2b

Combine like terms: -2b + 2b = 0
7 + 5b = -16 + 0
7 + 5b = -16

Add '-7' to each side of the equation.
7 + -7 + 5b = -16 + -7

Combine like terms: 7 + -7 = 0
0 + 5b = -16 + -7
5b = -16 + -7

Combine like terms: -16 + -7 = -23
5b = -23

Divide each side by '5'.
b = -4.6

Simplifying
b = -4.6

See similar equations:

| 3/4-1/3m=1/4 | | ln(x)+ln(7x)=8 | | 12/5x16/15 | | z=14 | | -4+13y+7=16+17y-25 | | (2/5)5x/2=72 | | X^3/(2x) | | 20(5+3x)=10x | | 2(5x)+5= | | 6(-9-x)=102 | | -3(x+4)=2(-3-7) | | 28x-12=4(6x-12) | | m^3-9*m^2+15*m+25=0 | | 4(-10+5x)=160 | | 9x-9=7x+19 | | -4-5x= | | 4y-5+y+29=8y+30-6y | | 5x(4x+4)= | | 4-8(y+6)=1-2y | | 9+17p-2=9p+97-2p | | 5v^2-24v=5 | | 1a+3b=9 | | 3/7=x/140 | | 1+2b-13=12-4b | | 6x-2x-4=2(x-1) | | -6-2-8=10 | | 3/8=-2/5a | | -5(-3x-7)=110 | | 11x+14=11x-14 | | 2z+9.75-7z=-5 | | 9n-7=65+n | | 12x+5y=217 |

Equations solver categories